THE ROLE OF DIGITAL MARKETING WITH CREATIVITY AND INNOVATION FOR SUSTAINABLE MSMEs - Yenny Maya Dora; Mohd Haizam Saudi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The impact of the Coronavirus disease (COVID-19) pandemic on SME and MSME businesses is enormous. With its implementation, you must wear a mask and keep your distance and reduce activities outside the home. This has in many companies being closed so that many companies are dismissed. This has an impact on the people's purchasing power of MSME products, which has decreased significantly. Many MSMEs have to close their businesses or go out of business. The purpose of this research is to find out the role of digital marketing for MSMEs to be sustainable and sustainable. This research method is descriptive and verification with a total sample of 405 SMEs and MSEs in the city of Bandung. The analytical tool used to analyze research data is to use SEM Amos. The results of this study state that digital marketing with creativity and innovation is very important for MSMEs to survive and be sustainable in the New Normal era.